HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PEMERIKSAAN KESEHATAN REPRODUKSI PADA PASIEN PENDERITA PENYAKIT MENULAR SEKSUAL DI PUSKESMAS HELVETIA KOTA MEDAN TAHUN 2015 - Yunida Turisna Octavia (Jurnal Online Keperawatan Indonesia, 2018)
Exually transmitted diseases (STDS) became the talk of such an important disease of AIDS cases appears after the swallow many of the victims died even now sexually transmitted disease is a disease that is transmitted to others through sexual contact. In Indonesia had many reports on the prevalence of STDS in 2010 to 2014 shows the prevalence of premenstrual syndrome and chlamydia infections is high between 20%-35%. In battle the disease syphilis rise primarily on women's sexual workers group. Figures for the incidence of the disease is increasing every year, the year 2012 of 15.4%, 18.9% in 2013 and 2014 into 22.1%. In number of PMS Helvetia Clinic in January up to December 2014 the most dominant 25-49-year-old totaled 968 people. The purpose of this research is to know the relation of knowledge and attitude to the action on the patient's reproductive health screening sexually transmitted diseases (STDS). This type of research is quantitative research with cross sectional approach. The population of this research are all PMS sufferers who visited reproductive health diPuskesmas checked for Helvetia Medan city as much as 2337 people by 2014 with monthly averages as many as 190 people and samples in this research is as much as 66 people by using the technique of accidental sampling. Analysis of the data by using the chi-square test with significance value of 10%. The results showed that the majority of knowledge is not good delightful 150%, the negative attitude of the majority to 59,1% and the majority of the action not good 62.1%. The conclusion that there is a relationship of knowledge (p = 0.000) value OR 10,607, attitudes (p = 0.003) value OR 4,848 with action examination of reproductive health in patients sexually transmitted diseases (STDS). In people with an STD in order to increase knowledge about STDS with how to request information from health workers and through social media, do a PAP Smear examination properly, which includes examination of vaginal fluid and bacteria-bacteria that cause sexually transmitted infections, HIV and prevent the transmission of STDS by wearing protective tools such as a condom if sexual intercourse. To the head of the clinic to do health promotion of reproductive health, especially to adolescents, mothers, distribute free condoms to masyarakat.